An alternative staining method for counting red-eared slider turtle (Trachemys scripta) blood cells using crystal violet in cells diluted with 0.45% sodium chloride. (September 2014) - Tsai, Chyong-Ying; Yu, Jane-Fang; Wang, Yu-Wen; Fan, Pei-Chia; Cheng, Ting-Yu; Wang, Lih-Chiann
Various staining methods are available for reptilian species blood cell quantification. However, these methods have shown inaccurate differentiation limitations. The current study evaluates staining effects and blood cell counting results using an alternative method, counting blood cells diluted with 0.45% sodium chloride solution and stained with crystal violet. Blood samples from 8 red-eared slider turtles ( Trachemys scripta ) were collected. Red and white blood cell counts were performed using different methods: the unstained method, the Unopette method, Liu stain, and crystal violet method using blood cells diluted in various sodium chloride solution osmolarities. The staining properties and blood cell count results were compared. The crystal violet method using blood cells diluted in 0.45% sodium chloride solution delivered the best staining and counting results among all of the tested methods, with the lowest average coefficient of variance. The proposed method can easily be performed, serving as a feasible method for blood cell counting in chelonians.